Laminin-1 (LM-111) in preeclampsia and systemic lupus erythematosus (2013)
Background: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the production of antibodies. SLE has been associated with placental pathology, a finding that is also the determinant in preeclampsia (PE). Genetic evidence and serologic reports suggest laminin-1 (LM-111) as an immunogenic molecule and its polymorphic gene as a candidate gene for both disorders. Objective: To evaluate the association between LAMA1 (rs543355) and LAMC1 (rs20563) polymorphisms and the presence of SLE and PE as well as to determine serum levels of anti-LM-111 autoantibodies in the PE group. Methods: Group A: 169 women with PE and 172 healthy pregnant women. Group B: 204 women with SLE and 204 healthy women. Anti-LM-111 for group A was measured by ELISA and the genotyping was done by using a PCR system. Results: Group A: Levels of anti-LM-111 was similar in women with PE and the control group (p = 0.3). The allelic frequencies and genotypes did not show statistically significant differences for LAMA1 and LAMC1 polymorphisms. Group B: Significant differences between SLE patients and controls for rs543355 polymorphism were not observed. Nevertheless, LAMC1 rs20563 A-allele provided protection against the development of SLE (OR 0.73, 95%CI 0.55-0.96). Conclusions: Serum levels of anti-LM-111 at the third trimester of gestation do not seem to have any direct relationship with the presence of PE, and the SNPs evaluated are not associated with the risk of developing this disorder. LAMC1 polymorphism could be a protective factor for SLE. © Informa UK, Ltd.